2018
DOI: 10.1186/s12943-018-0796-y
|View full text |Cite
|
Sign up to set email alerts
|

Function of the c-Met receptor tyrosine kinase in carcinogenesis and associated therapeutic opportunities

Abstract: c-Met is a receptor tyrosine kinase belonging to the MET (MNNG HOS transforming gene) family, and is expressed on the surfaces of various cells. Hepatocyte growth factor (HGF) is the ligand for this receptor. The binding of HGF to c-Met initiates a series of intracellular signals that mediate embryogenesis and wound healing in normal cells. However, in cancer cells, aberrant HGF/c-Met axis activation, which is closely related to c-Met gene mutations, overexpression, and amplification, promotes tumor developmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
340
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 423 publications
(345 citation statements)
references
References 105 publications
4
340
0
1
Order By: Relevance
“…Moreover, the malignant progression and high mortality rates associated with these tumors are related to their insidious onset, frequent metastasis and recurrence, and poor prognosis . Treatment on the basis of early diagnosis is still the main approach for achieving long‐term cancer‐free survival . Although many biomarkers of malignant tumors are currently used in the clinical setting, all of these biomarkers have limitations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the malignant progression and high mortality rates associated with these tumors are related to their insidious onset, frequent metastasis and recurrence, and poor prognosis . Treatment on the basis of early diagnosis is still the main approach for achieving long‐term cancer‐free survival . Although many biomarkers of malignant tumors are currently used in the clinical setting, all of these biomarkers have limitations.…”
Section: Discussionmentioning
confidence: 99%
“…[29][30][31] Treatment on the basis of early diagnosis is still the main approach for achieving long-term cancer-free survival. [32][33][34][35][36] Although many biomarkers of malignant tumors are currently used in the clinical setting, all of these biomarkers have limitations. Therefore, many studies have focused on identifying more effective biomarkers to improve the early diagnosis of ma- 55 Moreover, hsa_circ_0033155 could serve as a biomarker or therapeutic target in non-small-cell lung cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Malignant cell proliferation is one of the hallmarks of tumor cells [82][83][84][85][86]. Research has shown that c-Myc can promote the transcription of positive cell cycle regulatory factors, such as E2F transcription factors, cyclin D1, and cyclin-dependent kinase 4 (CDK4).…”
Section: Pvt1 Participates In the Proliferation-related Signaling Patmentioning
confidence: 99%
“…The BRAF gene is located on human chromosome 7q34 and encodes a serine/threonine protein kinase with a molecular weight of 67 kD-99 kDs [4]. This protein kinase is involved in regulating the transcriptional activity of cells during cell growth, division and differentiation, and it affects the regulation of cell morphology and the distribution of the cytoskeleton.…”
Section: Introductionmentioning
confidence: 99%